(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The body during normal metabolic function produces free radicals which are highly reactive species. Free radicals could also be introduced into the body from the environment. The oxidation induced by reactive oxygen species can result in DNA mutation, membrane protein damage and cell membrane disintegration. The present study assayed the preliminary phytochemicals, total phenolics and total flavonoids and free radicals scavenging ability of methanol extract of Jatropha tanjorensis leaf. Standard methods for determining phytochemicals, reducing power, nitric oxide scavenging, hydroxyl radical, and lipid peroxidation scavenging activity were employed. The phytochemical screening result revealed the presences of phenols, flavonoids, saponin, alkaloids, tannins, terpernoids and steroids. The total phenolic content of methanol extract of Jatropha tanjorensis leaf measured by Folin-Ciocalteau reagent in terms of gallic acid equivalent was 11.35±0.82mgGAE/g. The flavonoid content of the plant sample calculated as Quercetin equivalent was 15.91±1.60mgQCE/g. GC-MS results revealed relevant pharmacological bioactive compounds. The antioxidative activity of the plant’s extract correlated with total phenolic content. The radical scavenging activity showed a dose dependent increase in the reducing power. The minimum NO inhibitory activity was 8.88±0.63 at 200µg/ml and the maximum activity was 32.70±2.71 at 800µg/ml. The minimum percentage H2O2 radical inhibitory activity was 8.30±0.88 at 200µg/ml and a maximum activity was 22.80±2.28 at 800µg/ml. There was also an increase scavenging effect of lipid peroxide radical in concentration dependent manner. The results of this study indicate that the leaf of Jatropha tanjorensis possess antioxidant properties and could serve as free radical inhibitor